Analysis of the Role of Elementary School Teacher Learning Communities Using the Principles of "Community of Practitioners" in Negeri Besar District, Way Kanan Regency, Lampung Province - Fitri Yuliawati; Anita Ekantini; Inggit Dyaning Wijayanti; Shinta Melia Khorinimah (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2026)
This study aims to analyze the role of elementary school teacher learning communities using the principles of "Community of Practice" in Negeri Besar District, Way Kanan Regency, Lampung Province. This study uses a descriptive qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects consisted of elementary school/madrasah teachers, learning community coordinators, and teacher community members. The results show that learning communities play an important role in improving teachers' pedagogical, professional, social, and technological competencies. Learning communities also serve as a means of collaboration between teachers in sharing experiences, discussing learning problems, and finding joint solutions. The principles of the community of practice are implemented through regular discussions, learning reflections, sharing of good practices, and collaborative learning both online and offline. Despite several obstacles such as limited internet access, considerable distance between schools, and limited technological skills, the learning communities are still able to operate sustainably through the use of digital media such as WhatsApp, Zoom, Google Drive, and Google Docs. Thus, teacher learning communities based on communities of practice can be one strategy in improving the quality of education and the professionalism of elementary school teachers.